Three‐dimensional morphometric analysis of microglial changes in a mouse model of virus encephalitis: age and environmental influences. (26th June 2015) - de Sousa, Aline A.; dos Reis, Renata R.; de Lima, Camila M.; de Oliveira, Marcus A.; Fernandes, Taiany N.; Gomes, Giovanni F.; Diniz, Daniel G.; Magalhães, Nara M.; Diniz, Cristovam G.; Sosthenes, Marcia C. K.; Bento‐Torres, João; Diniz, José Antonio P.; et al.
Abstract Many RNA virus CNS infections cause neurological disease. Because Piry virus has a limited human pathogenicity and exercise reduces activation of microglia in aged mice, possible influences of environment and aging on microglial morphology and behavior in mice sublethal encephalitis were investigated. Female albino Swiss mice were raised either in standard (S) or in enriched (EE) cages from age 2 to 6 months (young – Y), or from 2 to 16 months (aged – A). After behavioral tests, mice nostrils were instilled with Piry‐virus‐infected or with normal brain homogenates. Brain sections were immunolabeled for virus antigens or microglia at 8 days post‐infection (dpi), when behavioral changes became apparent, and at 20 and 40 dpi, after additional behavioral testing. Young infected mice from standard (SYPy) and enriched (EYPy) groups showed similar transient impairment in burrowing activity and olfactory discrimination, whereas aged infected mice from both environments (EAPy, SAPy) showed permanent reduction in both tasks. The beneficial effects of an enriched environment were smaller in aged than in young mice. Six‐hundred and forty microglial cells, 80 from each group were reconstructed. An unbiased, stereological sampling approach and multivariate statistical analysis were used to search for microglial morphological families. This procedure allowed distinguishing between microglial morphology of infected and control subjects. More severe virus‐associated microglial changes were observed in young than in aged mice, and EYPy seem to recover microglial homeostatic morphology earlier than SYPy . Because Piry‐virus encephalitis outcomes were more severe in aged mice, it is suggested that the reduced inflammatory response in those individuals may aggravate encephalitis outcomes.